Gut microbiome and innate immune response patterns in IgE‐associated eczema. Issue 9 (September 2015) - West, C. E.; Rydén, P.; Lundin, D.; Engstrand, L.; Tulic, M. K.; Prescott, S. L.
Summary Background Gut microbiome patterns have been associated with predisposition to eczema potentially through modulation of innate immune signalling. Objective We examined gut microbiome development in the first year of life in relation to innate immune responses and onset of IgE‐associated eczema over the first 2.5 years in predisposed children due to maternal atopy [www.anzctr.org.au, trial ID ACTRN12606000280505]. Methods Microbial composition and diversity were analysed with barcoded 16S rRNA 454 pyrosequencing in stool samples in pregnancy and at ages 1 week, 1 month and 12 months in infants (n = 10) who developed IgE‐associated eczema and infants who remained free of any allergic symptoms at 2.5 years of age (n = 10). Microbiome data at 1 week and 1 month were analysed in relation to previously assessed immune responses to TLR 2 and 4 ligands at 6 months of age. Results The relative abundance of Gram‐positive Ruminococcaceae was lower at 1 week of age in infants developing IgE‐associated eczema, compared with controls (P = 0.0047). At that age, the relative abundance of Ruminococcus was inversely associated with TLR2 induced IL‐6 (−0.567, P = 0.042) and TNF‐α (−0.597, P = 0.032); there was also an inverse association between the abundance of Proteobacteria (comprising Gram‐negative taxa) and TLR4‐induced TNF‐α (rs = −0.629, P = 0.024). This relationship persisted at 1 month, with inverse associations between the relative abundance of Enterobacteriaceae (within the Proteobacteria phylum) and TLR4‐induced TNF‐α (rs = −0.697, P = 0.038) and Enterobacteriaceae and IL‐6 (rs = −0.709, P = 0.035). Mothers whose infants developed IgE‐associated eczema had lower α‐diversity of Bacteroidetes (P = 0.04) although this was not seen later in their infants. At 1 year, α‐diversity of Actinobacteria was lower in infants with IgE‐associated eczema compared with controls (P = 0.002). Conclusion and clinical relevance Our findings suggest that reduced relative abundance of potentially immunomodulatory gut bacteria is associated with exaggerated inflammatory cytokine responses to TLR‐ligands and subsequent development of IgE‐associated eczema.